Роман Олеся Гончара "Собор" як вияв "устремління людини до вічності" - Мех, Н. (Культура слова, 2018)
Авторка уводить текст роману Олеся Гончара «Собор» в
широкий мовно-культурний вимір. Вона розглядає твір як духовний
заповіт письменника, який привертає увагу читача до минулого
нашого народу, зокрема до часів козаччини.
Шана до славетних проявів українського духу на різних часових
зрізах історичного розвитку нації, народу, рішучість у збереженні
та плеканні духовних скарбів, любов до людей та Батьківщини – все
це ядерні поняття мови «Собору» Олеся Гончара. The article attempts to take a look at Oles Honcharʼs novel «The
Cathedral» in a broad linguistic and cultural sense. The work is
considered as a spiritual testament of the author. The novel is represented
by the eyes of contemporaries. Particular attention is paid to the past of
our people, in particular, the Cossacks.
Honoring the glorious manifestations of the Ukrainian spirit at
various time sections of the historical development of our people, the
determination to preserve and cultivate spiritual treasures, love for
people and the homeland – all this we see in the «eagle» «Cathedral»
Oles Honchar.